Centella asiatica Nanoparticles as Potential Acetylcholinesterase Inhibitor for Cognitive Decline Therapy using Ellman's Method: An in Vitro Study - Nathania, Nathania; Kusumaningrum, Selvina Cindy; I'tishom, Reny; Kumalasari, Feranita; Margiana, Ria (Folia Medica Indonesiana, 2024)
Highlights: 1. This research contributes novel data to current studies by combining the potential of Centella asiatica extract with PEG-400 to develop a therapeutic agent aimed at improving cognitive function through an effective drug delivery system capable of penetrating the blood-brain barrier. 2. The findings of this study revealed that the combination of Centella asiatica extract and PEG-400 at an adequate ratio exhibits great potential as an acetylcholinesterase inhibitor. Abstract Cognitive impairment, caused by neurocognitive changes and neuroinflammation, affects 65.6 million elderly people worldwide and can interfere with their quality of life. Centella asiatica is recognized for its neuroprotective potential due to its active compounds. This study aimed to investigate the acetylcholinesterase inhibitory properties of Centella asiatica as potential therapeutic agents for cognitive decline. Polyethylene glycol 400 (PEG-400) was used to achieve an effective drug delivery system of Centella asiatica extract, facilitating the inhibition of the apoptosis signaling pathway and allowing neuroprotective agents to cross the blood-brain barrier (BBB). This research involved several testing stages, including gas chromatography-mass spectrometry (GC-MS) to identify active compounds (e.g., tryptamine, γ-sitosterol, and β-sitosterol) that contribute to cognitive function improvement. Particle size analysis (PSA) tests were conducted on three formulations of the extract and PEG-400, with ratios of 1:100, 100:1, and 1:1, to determine the optimal formulation for subsequent testing. Scanning electron microscopy (SEM) was utilized to observe the morphology and surface structure of the samples, while Ellman's method was employed to test the ability of acetylcholine (ACh) in improving cognitive abilities. The results subsequently underwent descriptive analysis, particle distribution analysis, analysis of variance (ANOVA), nonparametric tests, image analysis, regression tests, multivariate analysis, and correlation tests. The synthesis demonstrated that the 1:100 formulation produced ideal-sized nanoparticles (5–7 nm), optimal for penetrating the BBB. The PSA and SEM analyses supported this finding by demonstrating homogeneous particle morphology and consistent chemical composition. The in vitro Ellman's assay revealed a high inhibitory rate of 97.63% for the 100:1 formulation. The 1:1 and 1:100 formulations demonstrated a very high effectiveness as acetylcholinesterase inhibitors. The combination of PEG-400 and Centella asiatica extract has great potential as an innovative pharmacological therapy for cognitive decline. However, further research is required to ensure the right dosage and development of the research findings.